Analysis of Factors Affecting Workload of Anesthesiologists In Indonesia - Parwati, Putu Atika; Arta, Sang Ketut (Sean Institute, 2022)
Anesthesiologist is one of the professions that work in the operating room in providing anesthesia nursing services and is considered as one of the medical specialties with a high workload. The purpose of this study was to determine the factors that influence the workload of anesthesiologists in Indonesia. The study design was cross-sectional. The population taken is anesthesiologist throughout Indonesia. The data analysis used is a binary logistic regression multivariate test. The results of the analysis revealed that most of the anesthesiologists had a low workload, namely 240 respondents (59.3%). Work patterns (adj. OR: 1.65) and number of working hours (adj. OR: 2.60) are factors that have a significant relationship with the workload of anesthesiologists.